A longer and healthier life with TOR down-regulation: genetics and drugs. (22nd March 2011) - Bjedov, Ivana; Partridge, Linda
Abstract : Genetic down-regulation of a major nutrient-sensing pathway, TOR (target of rapamycin) signalling, can improve health and extend lifespan in evolutionarily distant organisms such as yeast and mammals. Recently, it has been demonstrated that treatment with a pharmacological inhibitor of the TOR pathway, rapamycin, can replicate those findings and improve aging in a variety of model organisms. The proposed underlying anti-aging mechanisms are down-regulated translation, increased autophagy, altered metabolism and increased stress resistance.